Islam and Gender: Practicing Female Circumcision in Indigenous Communities (Case Study of Jepara Central Java): Social Dynamics of Kejawen Indigenous Peoples, Philosophy of Life of Kejawen Indigenous People, Jepara Kejawen Indigenous People's Response to the KUPI Decision (Prohibition of Female Circumcision) - Muh Rafi Alfaris (UIN Sulthan Thaha Saifuddin Jambi, 2025)
The purpose of this article is to examine the response of the Kejawen indigenous community in Banjaran Village Bangsri Subdistrict Jepara Regency, to the decision of the KUPI (Kongres Ulama' Perempuan Indonesia) to ban the practice of female circumcision in Jepara, where they have traditionally practiced female circumcision since the time of their ancestors. In fact, this ban is based on an in-depth study that female circumcision has more harmful effects. The research method used is field research, with an empirical legal approach. After all the data is collected, it is then analyzed using 3 stages such as data reduction, data display, and conclusion drawing. Based on the analysis, it can be concluded that the Kejawen indigenous people of Banjaran Village Bangsri Subdistrict Jepara Regency responded casually to the prohibition of female circumcision practices that had been decided by KUPI (Kongres Ulama' Perempuan Indonesia). They insist on continuing the practice of female circumcision as a preservation of the traditions of their ancestors.